(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The paper highlights combined techniques of strengthening that include geotextile laying as well as other related advanced technologies. Subgrade construction analysis and its modification, reinforced with the different types and options of combined strengthening were conducted. To justify strengthening of subgrade a series of numerical calculations were made. Simulation with software package SCAD has confirmed the experimental results. From obtained results one can conclude that minimum horizontal displacements are observed in the version with deepening of geotextile at 1m and vertical ones at 0.4 m. Based on simulation results it is possible to make recommendations concerning modernization of existing subgrade and construction of new one in complex engineering-geological conditions